2020
DOI: 10.1111/exd.14195
|View full text |Cite
|
Sign up to set email alerts
|

Stiffness measurement is a biomarker of skin ageing in vivo

Abstract: Due to the expansion of the ageing population, understanding age-related pathologies remains of great interest. The human skin is particularly affected by environmental stressors and goes through profound alterations that modify its appearance throughout ageing (for review, [1]). These modifications occur in the epidermis that becomes thinner due to reduced capacities in proliferation/differentiation, resulting in reduction of exchange surface. The alterations also arise in the dermis where the number of fibro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 18 publications
1
10
0
Order By: Relevance
“…ECM produced by and surrounding papillary dermis fibroblasts undergoes profound alterations during skin aging. The curled, thin, short, and loosely interwoven fibers become thicker and form network aggregates [253][254][255][256], leading to assessable changes in the overall tissue stiffness [257]. These changes are more severe in photo-exposed skin [242,254].…”
Section: Flattening Of Epidermal Rete Ridgesmentioning
confidence: 99%
“…ECM produced by and surrounding papillary dermis fibroblasts undergoes profound alterations during skin aging. The curled, thin, short, and loosely interwoven fibers become thicker and form network aggregates [253][254][255][256], leading to assessable changes in the overall tissue stiffness [257]. These changes are more severe in photo-exposed skin [242,254].…”
Section: Flattening Of Epidermal Rete Ridgesmentioning
confidence: 99%
“…Depending on its biomechanical properties, ECM can profoundly impact fibroblast survival, proliferation, migration and inflammatory signalling 14 . Thus, approaches that measure biomechanical skin properties across scales ranging from single‐cell to whole‐tissue can educate skin disease diagnosis 15 and serve as a biomarker of skin ageing 16 . Yet, the effects of ECM on fibroblasts are reciprocal, and the latter can significantly alter ECM biomechanics via contractility.…”
Section: Fibroblasts and Contractilitymentioning
confidence: 99%
“…In addition, this study showed that human consumption of ESM powder as a dietary supplement can produce ECM effects such as skin elasticity and improved respiratory function. Since skin aging is characterized by structural and functional changes such as wrinkles and loss of elasticity, and skin stiffness reflects reorganization of the ECM in the dermis (Runel et al 2020), mechanical properties and functional changes in the skin and lungs by ESM ingestion may indicate a shift to a younger ECM.…”
Section: Discussionmentioning
confidence: 99%